Transforming the character of public organizations : techniques for change agents - Rusaw, A. Carol, 1946- (Quorum Books, 1998)
The author argues that to inspire change in any organization and particularly in the public sector, agents must realize change is collective, non-rational and non-linear. Incorporating a phenomenological perspective, she provides real-life examples for public administrators.